Price Flexibility in Channels of Distribution: Evidence from Scanner Data - Shantanu Dutta; Mark Bergen; Daniel Levy (Bar-Ilan University, Department of Economics, 2002)
In this study, we empirically examine the extent of price rigidity using a unique store-level time series data set—consisting of (i) actual retail transaction prices, (ii) actual wholesale transaction prices which represent both the retailers' costs and the prices received by manufacturers, and (iii) a measure of manufacturers' costs—for twelve goods in two widely used consumer product categories. We simultaneously examine the extent of price rigidity for each of the twelve products at both, final goods and intermediate goods levels. We study two notions of price rigidity employed in the existing literature: (i) the frequency of price changes, and (ii) the response of prices to exogenous cost changes. We find that retail prices exhibit remarkable flexibility in terms of both notions of price rigidity. i.e., they change frequently and they seem to respond quickly and fully to cost changes. Furthermore, we find that retail prices respond not just to their direct costs, but also to the upstream manufacturers' costs, which further reinforces the extent of the retail price flexibility. At the intermediate goods level of the market, in contrast, we find relatively more evidence of rigidity in the response of manufacturers prices to cost changes. This despite the fact that wholesale prices change frequently and therefore exhibit flexibility according to the first notion of price rigidity.
Keywords: E12; E31; L16; 330; Price Flexibility/Rigidity; Intermediate and Final Goods Markets; Stages of Processing